2019
DOI: 10.1093/femsle/fnz113
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of a lincomycin-resistant plasmid between coagulase-negative staphylococci during soybean fermentation and mouse intestine passage

Abstract: Staphylococcus equorum is a benign bacterium and the predominant species in high-salt fermented food. Some strains of S. equorum contain antibiotic-resistance plasmids, such as pSELNU1 that contains a lincosamide nucleotidyltransferase (lnuA) gene and confers resistance to lincomycin. Previously, we showed that pSELNU1 is transferred to other bacteria under laboratory growth conditions. However, it is not known if the plasmid can be transferred to other bacteria during food fermentation (in situ) or during pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Antibiotic resistance can indirectly increase virulence, not directly, via quorum sensing [ 34 ]. Furthermore, acquired antibiotic resistance genes may be transferred to other bacteria during fermentation and intestinal commensal bacteria as they pass through the intestine [ 35 , 36 ]. Therefore, it is essential to check for the presence of transferrable antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotic resistance can indirectly increase virulence, not directly, via quorum sensing [ 34 ]. Furthermore, acquired antibiotic resistance genes may be transferred to other bacteria during fermentation and intestinal commensal bacteria as they pass through the intestine [ 35 , 36 ]. Therefore, it is essential to check for the presence of transferrable antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, antibiotic resistance genes can be transferred to other bacteria during fermentation. They can also be transferred to intestinal commensal bacteria as they pass through the intestine [ 52 , 53 ]. Therefore, it is essential to check for the presence of acquired antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
“…Here, plasmid pKS1030-3 from S. equorum KS1030 was used in assessment of gene transferability and biofilm formation. In gene transfer experiments, S. saprophyticus KM1053 was used as the recipient strain because it is resistant to tetracycline 11 . S. aureus RN4220 was used as an expression host for constructed plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…The lnuA gene was located on small plasmids, named pSELNU1–3, with only two different nucleotide sequences among these three plasmids 10 . Notably, although pSELNU1 is not a conjugative plasmid, pSELNU1 in S. equorum strain KS1030 was transferred to other Staphylococcus species, Enterococcus faecalis , and Tetragenococcus halophilus in vitro 10 , and was also transferred to S. saprophyticus during soybean fermentation (in situ) and passage through murine intestines (in vivo) under lincomycin pressure 11 . Recent complete genome sequencing revealed that S. equorum KS1030 also harbours plasmid pKS1030-3, which encodes elements facilitating gene mobility such as a relaxase 12 .…”
Section: Introductionmentioning
confidence: 99%